A web-based travel system using mashup in the RESTful design. (22nd August 2011) - Hsieh, Meng-Yen; Lin, Hua-Yi; Li, Kuan-Ching
According to the progress of web applications, websites are always designed toward facilitating interactive information sharing, establishing user-oriented service, and providing interoperability, and collaboration mechanisms. Colloquially, web applications in a service-oriented architecture are implemented as web services with XML-based protocols to provide plentiful information to users by object-oriented techniques. However, the above approach usually builds the complex and completed service combining and reusing separated function units instead of rapid development and URI-based service. This study establishes a travel website as a mashup-based web application based on an alternative approach as the architectural style of the website itself, representational state transfer. Using the mashup scheme, the proposed website is developed with the announced APIs of the third party to include rich service or resource from other web applications. The proposed case study also presented the efficient development with low cost and the effective finished features conforming users requirement. The advantages for the adopted schemes are described by implementing the proposed travel website.